Fine mapping of the flavonoid 3’,5’-hydroxylase gene controlling anthocyanin biosynthesis in pepper anthers and stems - Wang, Yixin; Wang, Zheng; Du, Heshan; Chen, Bin; Wang, Guoyun; Wang, Qian; Geng, Sansheng; Zhang, Xiaofen (Frontiers in Plant Science, 2023)
Pepper (Capsicum annuum L) is one of the most important vegetables grown worldwide. Nevertheless, the key structural and regulatory genes involved in anthocyanin accumulation in pepper have not been well understood or fine mapped yet. In this study, F1, F2, BC1P1, and BC1P2 pepper populations were analyzed and these populations were derived from a cross between line 14-Z4, which has yellow anthers and green stems, and line 14-Z5, which has purple anthers and stems. The results showed that the yellow anthers and green stems were determined by a single recessive locus called to as ayw. While, using preliminary and fine mapping techniques, ayw locus was located between markers aywSNP120 and aywSNP124, with physical distance of 0.2 Mb. The CA11g18550 gene was identified as promising candidate for the ayw locus, as it co-segregated with the yellow anthers and green stems phenotypes. CA11g18550 encodes a homolog of the F3'5'H (flavonoid 3',5'hydroxylase) anthocyanin synthesis structure gene. The missense mutation of CA11g18550 possibly resulted in a loss-of-function. The expression analysis showed that CA11g18550 was significantly expressed in the stems, leaves, anthers and petals in 14-Z5, and it's silencing caused the stems changing from purple to green. This study provides a theoretical basis for using yellow anthers and green stems in pepper breeding and helps to advance the understanding of anthocyanin synthesis.